Mechanical and tribological properties of spark plasma sintered Nb–Al2O3 composites. Issue 5 (1st March 2021) - Dotta, A.L.B.; Serafini, F.L.; Ordoñez, M.F.C.; Machado, I.F.; Farias, M.C.M.
Abstract: This work presents a study of the mechanical and tribological properties of niobium-alumina composites obtained by the spark plasma sintering with a uniaxial pressure of 50 MPa at 1400 °C. The microstructure and crystalline phases of sintered materials were determined by scanning electron microscopy and X-ray diffraction, respectively. Mechanical properties of the samples related to the stiffness, hardness, and fracture toughness were determined through the instrumented indentation and the Vickers indention tests. For the tribological study, alumina, alumina-15%Nb, and alumina-25%Nb materials were tested under dry reciprocating sliding conditions, at room temperature using a ball-on-disc configuration. A three-levels factorial design was used to conduct the wear tests, considering the combination of material compositions and applied load (5 N, 10 N, and 15 N of applied load) for two types of counterbody (52100 steel and Al2 O3 ). Niobium addition improved the fracture toughness and wear resistance of the alumina matrix composites. The index of brittleness that correlates the stiffness, hardness and fracture toughness of the materials decreased with niobium content. When sliding against the steel counterbody, composites exhibited a wear resistance two orders of magnitude higher than that of the monolithic alumina and specific wear rate values characteristic of the mild wear regime ( k lower than 10 −6  mm 3  (N m) −1 ). The higher wear resistance of composites was related to the tribofilm formation on worn surfaces, due to material transfer from the 52100 steel counterbody surface. Alumina showed a higher wear rate in comparison with niobium-containing composites, due to brittle fracture occurrence, mostly when sliding against the Al2 O3 counterbody at higher loads. Wear-regime maps as a function of the index of brittleness and severity of contact allowed the distinction of wear mechanisms of the studied materials and visualization of the improved wear resistance of the niobium-alumina composites.